Association between PR Interval, First‐degree atrioventricular block and major arrhythmic events in patients with Brugada syndrome – Systematic review and meta‐analysis. Issue 4 (14th May 2019) - Pranata, Raymond; Yonas, Emir; Chintya, Veresa; Deka, Hadrian; Raharjo, Sunu Budhi
Abstract: Background: Risk stratification in patients with asymptomatic Brugada Syndrome is challenging, and despite recent advances, there is no clear evidence. The first‐degree atrioventricular block was hypothesized to be a predictor of arrhythmic events. Measurement of the PR interval and diagnosing atrioventricular block from surface ECG is easy, noninvasive, and cost‐effective. We aimed to assess the latest evidence on PR interval or first‐degree atrioventricular block and major arrhythmic events related to Brugada Syndrome. Methods: We performed a comprehensive search in PubMed for "atrioventricular block" OR "PR interval" and "Brugada syndrome." We included studies that have a component of PR interval and/or first‐degree atrioventricular block and major arrhythmic events related to Brugada Syndrome including syncope/VT/VF/appropriate ICD shocks/ICD implantation. Results: We included 1526 subjects from 7 studies. Pooled mean difference of PR interval in 4 studies showed a significant difference [MD 10.77 ms (2.97‐18.57) P  = 0.007, moderate‐high heterogeneity I 2  = 53% P  = 0.08]. On sensitivity analysis by removing a study, it became MD 6.50 ms [1.97‐11.03], P  = 0.005, heterogeneity I 2  = 0% P  = 0.52. Indicating that PR interval was prolonged by small margin. Pooled analysis of the association between a first‐degree atrioventricular block and major arrhythmic events was significant [OR 3.33 (2.02‐5.50) P  < 0.001, low heterogeneity I 2  = 0% P  = 0.57]. Conclusion: First‐degree AV block is associated with more frequent major arrhythmic events in Brugada syndrome patients. PR interval seemed to be prolonged but is yet to be determined whether the PR interval association is still significant if it did not cross the first‐degree AVB threshold.